Competitive religious entrepreneurs: Christian missionaries and female education in colonial and post-colonial India - Lankina, Tomila V. (British journal of political science, 2013)
This article explores the influence of Protestant missionaries on male-female educational inequalities in colonial India. Causal mechanisms drawn from the sociology and economics of religion highlight the importance of religious competition for the provision of public goods. Competition between religious and secular groups spurred missionaries to play a key role in the development of mass female schooling. A case study of Kerala illustrates this. The statistical analysis, with district-level datasets, covers colonial and post-colonial periods for most of India. Missionary effects are compared with those of British colonial rule, modernization, European presence, education expenditures, post-colonial democracy, Islam, caste and tribal status, and land tenure. Christian missionary activity is consistently associated with better female education outcomes in both the colonial and post-colonial periods. (British Journal of Political Science/ FUB)